Exploring the role of non-financial risk management in strategy processes of large retail banks - C. Reimers; C. B. Scheepers (South African Journal of Business Management, 2016)
The consideration of risk in the banking industry generally involves the understanding of credit and financial risks. However, the occurrence of high-profile, non-financial risk events (such as system downtime and fraud) have resulted in negative financial and reputational implications for banks globally. These events have provided an opportunity for stakeholders to reflect on the consideration of non-financial risk. Therefore, the objective of this research was to understand the incorporation of non-financial risk management into the strategy process at retail banks, including the related benefits and challenges and the initiatives that have been (and require to be) undertaken. To this end, a qualitative research approach was conducted, using an exploratory design. Twelve banking subject matter experts were interviewed to explore their unique insights and experiences into the research problem. The research identified several challenges related to the consideration of operational and business risk. Key findings emerged including: the need for increased awareness of non-financial risk concepts, the need to balance risk management and business development, and the dangers of over-confidence in existing internal processes.
Keywords: 650